2022
DOI: 10.1097/md.0000000000031002
|View full text |Cite
|
Sign up to set email alerts
|

Dietary β-carotene and vitamin A and risk of Parkinson disease: A protocol for systematic review and meta-analysis

Abstract: Background: The beneficial effects of dietary β-carotene and vitamin A on Parkinson disease (PD) have been confirmed, but some studies have yielded questionable results. Therefore, this meta-analysis investigated the effect of dietary β-carotene and vitamin A on the risk of PD. Methods: The following databases were searched for relevant paper: PubMed, Embase, Medline, Scopus, Cochrane Library, CNKI, Wanfang Med online, and Weipu databases for the relevant paper from 1990 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The biochemical effect of nutrition on neurodegenerative disease has been recently reviewed in a systematic review, which reported that Mediterranean-like diets may protect neurons and slow neurodegeneration via several mechanisms of action [ 17 ]. Namely, the increased intake of polyphenols [ 44 ], resveratrol [ 45 ], omega-3 fatty acids [ 46 ], vitamin E, vitamin C [ 47 ], and carotenoids [ 47 , 48 ], from fruits and vegetables, olive oil, and red wine, has beneficial antioxidant and anti-inflammatory properties [ 19 ]. Another potential mechanism of action is via the modulation of gut microbiota by a diet high in fiber and polyphenols, which both increase the amount of beneficial bacteria in the microbial composition of the gut [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The biochemical effect of nutrition on neurodegenerative disease has been recently reviewed in a systematic review, which reported that Mediterranean-like diets may protect neurons and slow neurodegeneration via several mechanisms of action [ 17 ]. Namely, the increased intake of polyphenols [ 44 ], resveratrol [ 45 ], omega-3 fatty acids [ 46 ], vitamin E, vitamin C [ 47 ], and carotenoids [ 47 , 48 ], from fruits and vegetables, olive oil, and red wine, has beneficial antioxidant and anti-inflammatory properties [ 19 ]. Another potential mechanism of action is via the modulation of gut microbiota by a diet high in fiber and polyphenols, which both increase the amount of beneficial bacteria in the microbial composition of the gut [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Jamali et al, in a study on rats, showed that β-carotene has a therapeutic effect on PD conditions and inhibits the substantia nigra dopaminergic cell death [33]. In addition, Wu et al, in a meta-analysis study, concluded that consumption of dietary β-carotene, but not vitamin A intake, may have a protective effect against PD [34]. However, Hughes et al, in a prospective cohort study of 1036 people with PD, reported no significant association between dietary intakes of carotenoids and the risk of PD [35].…”
Section: Discussionmentioning
confidence: 99%
“…In their work on rats, Jamali et al showed that β-carotene has a therapeutic impact on diseases related to Parkinson's disease and prevents the death of dopaminergic cells in the substantia nigra [203]. Furthermore, Wu et al conducted a metaanalysis investigation and determined that the consumption of dietary β-carotene, rather than vitamin A intake, may provide a safeguarding effect against PD [204]. Nevertheless, Hughes et al conducted a meticulous investigation involving 1036 individuals with PD and found no substantial correlation between the consumption of carotenoids through food and the likelihood of developing PD [205].…”
Section: Nutritional Supplements Focused On Recoverymentioning
confidence: 99%